Representações do somático e do psíquico na cultura de uma organização universitária e hospitalar brasileira - Abud, Cristiane Curi (2011)
Care experience in Programa de Atendimento e Estudos de Somatização do Departamento de Psiquiatria da UNIFESP/ HSP and scientific literature show that somatizing patients tend to establish an expensive relationship to hospital organization, increasing material and emotional costs. From the case study of Hospital São Paulo (HSP) and the Universidade Federal de São Paulo (UNIFESP), this work analyzed, qualitatively, which factors these organization’s culture offer to its community to allow them to build and to integrate social representations on psychic and somatic issues. Through psycossociologic methods analyses, it was noted that these organizations do not provide a culture that would help its members to deal with the anguish roused by the medical task, while dealing with somatization disorder patients. This task usually waves the possibility of death, determining hypochondria as its main anguish.